STUDYING ON EXPRESSION AND IDENTIFICATION OF HUMAN INSULIN IN E. coli - Chi, Phan Văn; Huyền, Bùi Thị; Phủng, Lê Văn (Vietnam Journal of Science and Technology, 2012)
SUMMARY Insulin is a hormone that produced by beta cells in the pancreas and regulated the glucose blood levels. Briefly, our strategy for the gene construction and expresion is described as follow. pET14bInsA vector contained gene A that encoding for the A peptide chain and pET14bInsB vector contained gene B that encoding for the B peptide chain. These vectors and the expression pET-32c(+) vector were digested by NcoI and BamHI. The released insulin A/B fragment and the opened plasmid pET-32c(+) were purified and ligated by T4 DNA ligase at 22oC, overnight. The resulting recombinant plasmid pET32cInsA/B was transformed into the E. coli BL21(DE3) strain. The expression of the fusion protein was observed by induction with 1 mM IPTG and analysed by SDS-PAGE. Two new protein bands with the size of aproximately 22 kDa (equvalent the size equvalent the size of fusion A) and 23 kDa (the size of fusion B) were then excised and digested with trypsin overnight. The results of identifying by NanoLC-MS/MS (Nano Liquid Chromatography – Tandem Mass Spectrometry) showed that the recombinant protein was truely the fusion A(B)-Trx that contained different peptides from chain A/B and thioredoxin. This result is an evidence to confirm the successful construction and expression of chain A/B of insulin in the fusion form in E. coli with pET-32c(+) vector. Key words. Insulin; pET-32 c(+); E. coli BL21 (DE3); NanoLC-MS/MS